THE PROBLEM OF ECOLOGICAL CONSCIOUSNESS AS A SUBJECT OF PSYCHOLOGICAL RESEARCH - Akramov Mirmukhsin Rustamovich (American Journals Publishing, 2024)
This article discusses research questions devoted to the study of increasing the effectiveness of methods of forming environmental representations in students and improving their methodological aspects.
Keywords: Ecological consciousness, environment, ecological representation, climate, naturalphil, moral introject, existential reality.